(untitled) (Heritage, 2023)
Nearly thirty years after the Dayton Peace Agreement, questions continue to arise about the functionality and future of Bosnia and Herzegovina. This is due to its excessive and dysfunctional administration, growing citizen distrust in institutions, and the inability of constituent nations to reach a basic consensus. Through an analysis based on the theoretical framework of ’weak’ and ’strong’ states, we aim to determine the nature of the Bosnia and Herzegovina as a state. We will evaluate its capacity to fulfill core state functions and address significant societal issues. The initial section of the paper will introduce the theoretical framework along with its key elements and dimensions, which assist in discerning whether a state is weak or strong. Subsequently, we will delve into an analysis of Bosnia and Herzegovina, its institutions, and its capabilities across three pivotal dimensions: stability and security, the efficacy of public service provision, and the aspect of social cohesion